Risk Factors for Pneumonia in Children Under Five at Komfo Anokye Teaching Hospital - Darkwa, A.G. (University of Ghana, 2012)
Background: Pneumonia kills more children under-five than AIDS, malaria and measles combined and yet has received far less attention. Each year, more than two million children under-five die of pneumonia in the developing world, compared to an estimated 800,000 children who die from malaria and around 300,000 children under-five who die from AIDS. In Ghana, pneumonia is one of the leading causes of death of under-five mortality and morbidity. Most mothers or care givers do not recognize the danger signs of pneumonia and realize the need for immediate medical care. Identification of modifiable risk factors may help reduce the disease burden. The objectives of this study are to study some of the environmental, nutritional and socio-demographic factors contributing to risk of pneumonia in children under five and to assess knowledge of mothers on health information about pneumonia. Methods: A case-control study was conducted at Komfo Anokye Teaching Hospital. We investigated 228 children, 114 cases and 114 controls. A structured questionnaire was administered to consenting mothers or caretakers of each case or control from March 2012 to May 2012. A case definition of pneumonia as given by World Health Organization (WHO) was used for cases and children without pneumonia or any respiratory disease seen at the Pediatric Out-patient department were enrolled as controls. Data was entered into MS Excel and imported into SPSS version 16 and Epi Info version 3.5.1. for statistical analysis. Results: 228 children including 114 cases and 114 controls were enrolled in the study. On univariate analysis, low maternal educational level (Odds Ratio (OR) =5.37, 95% Confidence Interval (CI) =2.09-14.14), overcrowding (OR=2.20, 95 % CI=1.22-3.99) and cooking fuel other liquid petroleum gas (OR=3.98, 95% CI=2.21-3.99) were the significant risk factors. Logistic regression analysis identified attendance at day-care center (OR=3.16, 95% CI=1.54-6.46) as the significant risk factor. Children under five with low birth weight, partial/no immunization, partially breastfed, exposed to tobacco smoke or weaned before six months or malnourished were likely of getting pneumonia but association was not significant. There was no association between gestational maturity status, sex and age of mother. Of the 228 mothers, 153(67.11%) have heard about pneumonia, 142(62.28%) believed exposure to cold weather and only 32(14.04%) said a germ causes pneumonia. 68(29.28%) know chest in-drawing, 137(60.89%) agreed fast breathing or difficult breathing and 22(9.65%) know breastfeeding as a preventive measure. Conclusion: The present study identified low maternal age, overcrowding, cooking fuel other liquid petroleum gas and attendance at day-care center as risk factors for pneumonia in children under five at Komfo Anokye Teaching hospital. A lot of the mothers have heard about pneumonia but few know about the danger signs/symptoms, causes as well preventive measures for pneumonia The information can be used to reduce the burden of pneumonia by effective education of the mothers and through appropriate public health measures.
Thesis (MPH) - University of Ghana, 2012